Once Upon a Christmas Cheery, in the Lab of Shakhashiri - Shakhashiri, Bassam Z. (1983)
One of many in a series of annual Christmas lectures given by Bassam Z. Shakhashiri, a Lebanese chemistry educator who spent most of his career at the University of Wisconsin-Madison. The 1980 lecture focuses more on kitchen chemistry, like determining the pH levels of common household items, water softening, how fire extinguishers work, the chemistry behind the formation of glass (with a glassblowing demonstration from Chemistry professor Charlie Amling), and the properties of rubber. With appearances by Bucky, the UW mascot; Santa Claus; and UW chemistry professor Fred Juergens. This video was taken from a DVD, which itself was made from an unknown magnetic tape. Any distortions in the image and sound of the video are inherent in the DVD itself.
Keywords: Science--Study and teaching; Lectures; Chemistry--Experiments; University of Wisconsin--Madison; Christmas; Santa Claus (Fictitious character); Glass blowing and working